2020
DOI: 10.1071/sh19140
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Neisseria gonorrhoeae in Jakarta, Indonesia: a cross-sectional study

Abstract: Background Neisseria gonorrhoeae has developed resistance to various antimicrobials. At least 10 countries have reported treatment failures with extended-spectrum cephalosporins. Periodic surveillance is essential to determine local treatment guidelines. This study was conducted to determine the resistance of N. gonorrhoeae to penicillin, tetracycline, levofloxacin, cefixime and ceftriaxone among the high-risk population for acquiring STIs in Jakarta and to identify factors associated with resistance. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
2
2
1
Order By: Relevance
“…18,19 Other studies from Jakarta and Thailand observed no isolates with RS to cefixime. 8,22 Our results demonstrated a lower mean IZD of cefixime (31.1 mm) compared to that reported for Vietnam (36.3 mm). 18 No gonococci isolates with resistance to azithromycin were observed in this study.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…18,19 Other studies from Jakarta and Thailand observed no isolates with RS to cefixime. 8,22 Our results demonstrated a lower mean IZD of cefixime (31.1 mm) compared to that reported for Vietnam (36.3 mm). 18 No gonococci isolates with resistance to azithromycin were observed in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…9 Other studies from Jakarta, Laos and Thailand observed no isolates with RS to ceftriaxone. 8,21,22 Our results show a lower mean IZD of ceftriaxone (37.5 mm) compared to that reported by Adamson et al for Vietnam (41.1 mm). 18 In our study, 31.6% of gonococci isolates had RS to cefixime.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…5 Penelitian Wresti dkk di Jakarta tahun 2018, pada 35 pasien didapatkan hasil kultur 97,1% resistensi terhadap penisilin dan 34,3% resistensi terhadap levofloksasin. 6 Berdasarkan penelitian Rizal Y tahun 2011 di RSUP Dr. M. Djamil Padang pada 26 pasien uretritis gonore, resistensi levofloksasin sebesar 73,1%, ofloksasin 61,5%, kanamisin 23,1%, sefiksim 73,1%, siprofloksasin 31,8%, seftriakson 53,8%, serta tiamfenikol 46,2%. 8 Luasnya resistensi antibiotik mengarah pada multidrug-resistant (MDR) atau extensively drugresistant (XDR).…”
unclassified